ANALYSIS OF THE INFLUENCE OF THE CREATIVE ECONOMY ON THE ECONOMY OF THE PEOPLE OF PEMATANG SERAI VILLAGE, TANJUNG PURA DISTRICT, LANGKAT REGENCY THROUGH HUMAN RESOURCE MANAGEMENT - Erwansyah, Erwansyah; Robain, Wilchan; Siregar, Mira (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2023)
The current economic era is called the era of the creative economy. This study aims to analyze the influence of the creative economy on the community's economy through human resource management.  The research location is in Pematang Serai Village, Tanjung Pura District, Langkat Regency. This research uses a  descriptive method with a qualitative approach. The sample in this study was 30 respondents. The results of the study explained that based on the results of the direct effect  of the  Creative Economy, it has a positive and significant effect on Human Resource Management. The Creative Economy has a positive and significant effect on the Community Economy. Human Resource Management has a positive and significant effect on the Community Economy. Meanwhile, based on the results of  the indirect effect of  the Creative Economy, it  has a positive and significant effect on the Community Economy through Human Resource Management.